Computation-assisted SiteFinding- PCR for isolating flanking sequence tags in rice - Hongru Wang; Jun Fang; Chengzheng Liang; Minghui He; Qiye Li; Chengcai Chu (BioTechniques)
SiteFinding-PCR is a method for isolating flanking sequence tags (FSTs) of T-DNA insertion lines, but the efficiency needs to be improved. Here we report a computation-assisted design for the random primers used in SiteFinding- PCR. A short sequence, GCATG, was screened from the rice genome and used as the 3′ end of the random primer. When applying the optimized primer for isolating FSTs from 168 transgenic rice lines, we obtained 107 specific products, including 64 FSTs. The efficiency of obtaining FSTs using the modified version of SiteFinding-PCR increased by 73.0% compared with the method previously reported (P < 0.01, µ test). We also provide computational results for several other plant species such as maize, sorghum, Arabidopsis, foxtail millet, and Brachypodium based on the available genome data, so that the modified method could be easily adapted to other species.